MANAGEMENT OF INNOVATIVE ACTIVITIES IN SERVICE ENTERPRISES AND STRATEGIES FOR ENHANCING COMPETITIVENESS - Bahodirov Shohruh Bahodir o‘g‘li (Web of Journals Publishing, 2025)
The article analyzes the importance of innovative approaches and management strategies in increasing the competitiveness of service enterprises. It examines the impact of service sector growth, increased investment volume, and the implementation of digital technologies and automation on economic development. The research results highlight the significance of innovative management strategies, competitive advantages, and technological modernization for the sustainable development of the service sector.
Keywords: Service sector, innovation, competitiveness, management, economic development, investments, digitalization, automation, technological development, service diversification, customer-oriented strategy, government support, export, sustainable development.